EFFECT OF FEEDING FREQUENCY OF CHICKEN INTESTINE PASTE ON THE GROWTH AND SURVIVAL OF GLASS CATFISH (Kryptopterus lais) FINGERLINGS - Anisya Putri Elmira; Khairul Hadi; Rosyadi Rosyadi; Agusnimar Agusnimar (Media Akuakultur, 2026)
This study evaluated the effect of feeding frequency of chicken intestine paste on the growth and survival of Kryptopterus lais fingerlings. The experiment utilized a completely randomized design with five feeding frequency treatments (2, 3, 4, 5, and 6 times per day) and three replications over 21 days. Ten fingerlings weighing 0.09±0.01 g were stocked in each aquarium and fed at a rate of 10% of their body weight per day. Observed parameters included growth performance, feed efficiency, feed conversion ratio, survival rate, and water quality. The results showed that feeding frequency had a significant effect on growth performance (P<0.05). Feeding four times day⁻¹ resulted in the best performance, indicated by a weight gain of 0.12±0.01 g, length gain of 1.14±0.21 cm, SGR of 0.57±0.01% day⁻¹, feed efficiency of 47.56±3.45%, feed conversion ratio of 2.48±0.21, and survival rate of 76.67±15.28%, with all water quality parameters remaining within optimal ranges. Therefore, a feeding frequency of four times day⁻¹ is recommended to improve growth and feed efficiency during the nursery phase of Kryptopterus lais.